Improve of recovery during the training process of shot-bullet - Petruk I.D (Kharkov National Pedagogical University, 2010)
Special features of the restorative means during the training of shot-bullet are described. Author made analysis of special literature, compares and assessments combination means of recovery, recommends to apply the complex of restorative means. The processes of sportsmen recovery became better during combination of sport massage and functional music, using the complex of facilities during a stage level of recovery.